An Overview of Community Behavior Towards Self-Medication for Diarrhea Drugs in Risa Village, Woha District, Bima Regency - Megawati Megawati; Muhammad Farid Hasyim; Marselina Sabu Ruron (Jurnal Farmasi Sandi Karsa, 2023)
Self-medication or self-medication is part of the community's efforts to treat minor ailments by using over-the-counter drugs, limited over-the-counter drugs and mandatory pharmacy drugs without consulting a doctor first. Diarrhea is a mild disease that can be treated with self-medication. The method used in this research is descriptive method, namely research that covers surveys with data collection techniques in the form of questionnaires. This research was conducted in Risa Village, Woha District, Bima Regency. This research was conducted in March 2023 using a questionnaire on 140 respondents according to the criteria. The results of this study indicate that the community's behavior towards diarrhea drug self-medication in Risa Village, Woha District, Bima Regency is classified as good with a percentage level of 95.13%.